THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF NHT (NUMBERED HEADS TOGETHER) OF STUDENT AT SMP MUHAMMADIYAH 2 KALASAN - Dian Sulistya Ningrum; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was done because the results of students' mathematics learning are still relatively low. Students are reluctant to ask about the material they have not understood that the learning outcomes obtained less optimal. This research aims to determine the results of learning mathematics using of cooperative learning model type of NHT (Numbered Heads Together) of student grade VIII at SMP Muhammadiyah 2 Kalasan Sleman Regency of Even Semester in Academic Year of 2015/2016. This was design is Posttest-Only Control Design. The population in this research were students class VIII SMP Muhammadiyah 2 Kalasan Sleman Regency. Samples of this research using random sampling techniques derived from class VIII A as an experimental class and VIII C as the control class. The data collection is done with the test method. A testing instrument using a validity test and reliability test. Data were analyzed before using hypothesis testing with a t-test first using analysis prerequisite test including normality test, and homogeneity test. Based on calculations by the significant level   and the degrees of freedom 65, we concluded that: (1) There are differences in learning outcomes of students learning math using cooperative learning model type of NHT with learning using conventional learning model. This is indicated by the results of the first test of the hypothesis that  and , so that . (2) The type of cooperative learning model NHT more effective than the conventional learning model. It is shown on the second hypothesis that the test results  and , so   .